2012
DOI: 10.1074/jbc.m111.292722
|View full text |Cite
|
Sign up to set email alerts
|

miR-30 Family Members Negatively Regulate Osteoblast Differentiation

Abstract: Background: microRNAs (miRNAs) are closely related to osteogenesis. Results: miR-30 family members (miR-30a, -30b, -30c, and -30d) mediate the inhibition of osteogenesis by targeting Smad1 and Runx2. Conclusion: miR-30 family members are key negative regulators of BMP-2-mediated osteogenic differentiation. Significance: These findings may provide new insights into understanding the regulatory role of miRNAs in the process of osteogenic differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 40 publications
7
129
0
4
Order By: Relevance
“…Other in vitro studies have elucidated a regulatory loop involving miR-31, Runx2, and Satb2 (special AT-rich sequence-binding protein 2): downregulation of miR-31 expression by Runx2 in differentiating bone marrow MSCs (BMMSCs) facilitates osteogenic commitment due to an increase in SATB2 protein expression (Deng et al 2013). Additionally, miR-30 family members have been widely studied as regulators of osteoblast differentiation, mainly through the suppression of the expression of Smad1 and Runx2 transcription factors (Zhang et al 2011a, Wu et al 2012, Eguchi et al 2013.…”
Section: Mirnas and Osteoblast Differentiationmentioning
confidence: 99%
“…Other in vitro studies have elucidated a regulatory loop involving miR-31, Runx2, and Satb2 (special AT-rich sequence-binding protein 2): downregulation of miR-31 expression by Runx2 in differentiating bone marrow MSCs (BMMSCs) facilitates osteogenic commitment due to an increase in SATB2 protein expression (Deng et al 2013). Additionally, miR-30 family members have been widely studied as regulators of osteoblast differentiation, mainly through the suppression of the expression of Smad1 and Runx2 transcription factors (Zhang et al 2011a, Wu et al 2012, Eguchi et al 2013.…”
Section: Mirnas and Osteoblast Differentiationmentioning
confidence: 99%
“…Наиболее изучено влияние мкРНК на транскрипционный фактор, участвующий в регулировании остеобластогенеза, RUNX2 (фактор транскрипции 2, содержащий домен Runt). К груп-пе мкРНК, блокирующих дифференцировку остеобластов посредством влияния на RUNX2, относятся мкРНК23а [37], мкРНК30а-d [38], мкРНК135а [39], мкРНК204 [40], мкРНК335 [41], мкРНК433 [42], мкРНК34с, мкРНК133а, мкРНК137, мкРНК205, мкРНК211, мкРНК217 [43,44]. Некоторые мкРНК со схожими функциями образуют кла-стеры: например, кластер мкРНК23а-27а-24-2, который является одним из основных в регуляции остеобластоге-неза.…”
Section: роль мкрнк в костном ремоделированииunclassified
“…Таргетная молекула Источник мкРНК, стимулирующие дифференцировку остеобластов мкРНК27, микроРНК142-3p APC [51,52] мкРНК29a Дкк1, KREMEN2, сФРЗ2, SPARC [48,54] мкРНК29b COL1A1, COL5A3, COL4A2, HDAC4, ТФРβ3, ACVR2A, CTNNBIP1, DUSP2 [55] мкРНК218 SOST, Дкк2, сФРЗ2 [49] мкРНК335-5p Дкк1 [50] мкРНК, блокирующие дифференцировку остеобластов мкРНК23a RUNX2, SATB2 [37,43,44] мкРНК30a-d RUNX2, SMAD1 [38,43,44] мкРНК34c, мкРНК133a, мкРНК137, мкРНК204, мкРНК205, мкРНК211, мкРНК217, мкРНК335, мкРНК338, мкРНК433, мкРНК3077-5p RUNX2 [39][40][41][42][43][44]53] мкРНК93 OSX [47] мкРНК135a RUNX2, SMAD5 [39,43,44] мкРНК155 SOCS1 [56] Примечание. APC -аденоматозная полипозная палочка; Дкк1 и 2 -Диккопф 1 и 2; KREMEN2 -кринглсодержащий трансмембран-ный белок; сФРЗ2 -секреторный белок, связанный с фризельдом 2; SPARC -секретируемый белок, кислый, богатый цистеином (остеонектин); COL1A1 -коллаген, тип I, α 1; COL5A3 -коллаген, тип V, α 3; COL4A2 -коллаген, тип IV, α 2; HDAC4 -гистонде-ацетилаза 4; ТФРβ 3 -трансформирующий фактор роста β 3 ; ACVR2A -рецептор типа 2А к активину А; CTNNBIP1 -белок, взаимо-действующий с β-катенином, 1; DUSP2 -фосфатаза двойной специфичности, тип 2; SOST -склеростин; RUNX2 -фактор транс-крипции 2, содержащий домен Runt; SATB2 -ДНК-связывающий белок; SMAD1 и 5 -семейство SMAD тип 1 и 5; OSX -остерикс; SOCS1 -супрессор цитокиновых сигналов 1.…”
Section: мкрнкunclassified
“…18 These miRNAs are also reported as osteomiRs that regulate osteoblast differentiation. 49 We have shown that miRNA-30s are downregulated in MDA-B02 cell line, a sub-population of the parental MDA-MB-231 breast cancer cells that specifically form bone metastasis in mice. 50 Restoring miRNA-30s in these cells decreased bone metastasis in vivo predominantly through the downregulation of genes associated with osteomimicry, such as integrinb3, CTGF, cadherin-11, connexin 43 and RunX2.…”
Section: Mirnas Regulate Bone Marrow Invasion and Colonisation By Canmentioning
confidence: 99%